Gasterophilus flavipes (Oestridae: Gasterophilinae): A horse stomach bot fly brought back from oblivion with morphological and molecular evidence - Li, Xin-yu; Pape, Thomas; Zhang, Dong (PloS one, 2019)
Species of Gasterophilus Leach are obligate parasites in domestic and wild equids and responsible for cosmopolitan gasterophilosis. Although with only eight species known so far, they have received considerable attention because of their significant veterinary and economic importance. Surprisingly, we found that G. flavipes (Olivier) is a valid species based on morphological characters from male, female and the egg, after spending half a century as a synonym of G. haemorrhoidalis (Linnaeus). In the present study, G. flavipes, G. haemorrhoidalis and G. inermis (Brauer), which are the three closely related species possessing a remarkable mixture of shared morphological characters, are diagnosed and comparatively redescribed; the key to separate adults and eggs are provided, together with a series of high-resolution photographs from all the body parts. COI barcodes do not allow for a separation of G. flavipes, G. haemorrhoidalis and G. inermis, but showed a closer relationship between G. flavipes and G. haemorrhoidalis than the other two combinations, which is consistent with the morphological evidence. Geographically, G. flavipes seems to be common and widespread in the warmer parts of the Palaearctic region. Thus, the epidemiology of gasterophilosis where G. flavipes is known or supposed to occur calls for a more careful veterinarian re-assessment. A decline in the populations of Gasterophilus spp. has been noticed in Europe, but all seven Palaearctic species of Gasterophilus appear to maintain stable populations in Xinjiang (China), which may be explained by a higher biodiversity of equids and less use of anti-parasitic treatments in Xinjiang than in Europe. Our study shows that morphological characters still provide the solid backbone in classification of Gasterophilus at species-level, and updated diagnoses and a key is provided to distinguish G. flavipes, G. haemorrhoidalis and G. inermis, and to facilitate studies of epidemiology, phylogeny and host-parasite co-evolution.